Supporting Preservice Elementary Teachers in Teaching Science for Equity and Justice: A Practical Framework - Davis, Elizabeth (Innovations in Science Teacher Education, 2022)
Preservice elementary teachers bring many strengths to science teaching but may not get extensive support in learning to work toward equity and justice in their science teaching. Drawing on four approaches to equity from a recent report from the National Academies of Sciences, Engineering, and Medicine (2022), this article presents a practical framework for helping preservice elementary teachers in this challenging work. The article first explores each approach, suggesting interpretive frames and teaching moves that preservice teachers could use in moving from a relatively abstract call for equity to making concrete decisions in elementary science instruction. A practical framework is developed based on that exploration, with a description of how the framework has been used instructionally in an elementary science methods class. Then, the article presents the results of a pilot study of 31 preservice elementary teachers’ use of a pilot framework, illustrating how these participants’ lesson plans readily reflected teaching moves focused on increasing children’s opportunity and access to science learning and increasing achievement, representation, and identification but less often reflected moves oriented toward broadening what counts as science or bringing science and justice together. The article concludes by noting that research is needed to further explore the utility of this framework and how equity can be supported in science teacher education more generally. The article also urges the field to develop representations of practice and elementary science curriculum materials that would support teachers in this challenging, lifelong work to advance equity and justice.